Use of sintilimab in primary adenosquamous carcinoma of the liver results in pathological complete response: a case report and literature review - Bai, Zhiqing; Chen, Yu-Ann; Xiao, Ying; Song, Jianping; Song, Jianwei; Xiang, Canhong (Frontiers in Immunology, 2025)
Adenosquamous cell carcinoma (ASC) is a rare and aggressive malignant tumor which consists of both adenocarcinoma (AC) and squamous cell carcinoma (SCC) component types. Although ASC can sometimes develop in the stomach, pancreas, gallbladder and thyroid, it rarely occurs in the liver. As such, primary ASC of the liver remains a poorly understood malignancy due to both the paucity of reported cases and scarcity of available published data. As such, while the use of immune checkpoint inhibitors (ICIs), including PD-1 and PD-L1 antagonists, has profoundly changed the treatment paradigm and outcomes in most tumors, there is virtually no previous documentation for the application of ICIs in the treatment of primary hepatic adenosquamous carcinoma. Herein, we report a clinical case of a 54-year-old woman with metachronous double primary tumors, one of which was dMMR ASC of the liver and received 8 cycles of single-agent immunotherapy using sintilimab. The post-treatment response was evaluated as a pathological complete response (pCR).